(untitled) (Research, Society and Development, 2022)
Critical patients are those who present imminent risks to life and require continuous care. These patients often need to be kept under Mechanical Ventilation (MV) to maintain respiratory functions. Tracheal aspiration is considered an invasive, mechanical and manual technique, used for the removal of secretions in individuals who cannot adequately remove pulmonary, tracheobronchial and/or oropharyngeal secretions. The current study, taking into account the scientific literature, aimed to show the possible complications due to performing tracheal aspiration in a patient with a critical health condition. This is an integrative literature review, carried out in October and November 2022 through electronic searches in the Google Scholar database. The search strategies allowed identifying 406 articles, applying the exclusion criteria, 398 were excluded, in total 8 articles were selected because they met all the requirements. The results show that this procedure can result in several complications mainly due to improperly performed techniques, including cardiac arrest, hypoxemia, dysrhythmias, arterial hypotension and pulmonary collapse. As well as the occurrence of complications such as atelectasis and pneumonia associated with the use of a mechanical ventilator, they can be minimized. It is concluded that tracheal aspiration is commonly used in patients with critical health, especially those who are hospitalized in the Intensive Care Unit, and that despite providing benefits to their health, it can also lead to several complications.